Efeitos de diferentes tipos de poda nos teores de nutrients emflores e frutos de goiabeira - Souza, Henrique A. de; Rozane, Danilo Eduardo; Romualdo, Liliane Maria; Natale, William (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2012)
A better understanding of the differences between the levels of nutrients, depending on the type of pruning used in the cultivation of the guava tree, may allow a more adequate understanding of the physiological processes of this fruit. The analysis of flowers is a tool that can be used to assist in assessing the nutritional status of crops, especially perennials. We evaluated the effects of different types of pruning on nutrient concentrations in flowers and fruit, at different developmental stages and in different parts of the fruit. The study was carried out in Vista Alegre do Alto, in orchards of guava variety Paluma. Flowers and fruit were collected in orchards, one under heavy pruning and the other with continuous pruning. The fruit were collected in two stages (two millimeters length and mature) and divided into basal part and apex, with the top toward the stalk. Flowers were collected in the same orchards as the fruits, sampling the basal part and apex of the flowers. F tests were performed and, when necessary, the Scott-Knott test at α= 5%. Overall, there were nutritional differences among flowers and fruits in relation to the type of pruning employed; drastic pruning provided higher levels of nutrients compared with continuous pruning. In relation to the portion of the samples, especially for fruit, there were differences between the apex and base, as well as between different stages of fruit collection.
Differences among nutrients in flowers and fruits of guava trees under different types of pruning
Keywords: Guava; Nutritional state; Psidium guajava